2015
DOI: 10.1039/c5tc00682a
|View full text |Cite
|
Sign up to set email alerts
|

Porosity-induced emission: exploring color-controllable fluorescence of porous organic polymers and their chemical sensing applications

Abstract: Most organic dyes dissipate their excitation energy in the aggregated state because of "aggregation caused quenching" effect, deteriorating their application in optoelectronic devices. To prevent "aggregation caused quenching" effect, we incorporate a dye-based fluorophore into a porous organic polymer skeleton because porosity would breed the spatial isolation of fluorophores to maintain its emission. Tuning the fraction of fluorophores in the skeleton of FL-SNW-DPPs would range the emission color covering fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 44 publications
(77 reference statements)
0
32
0
Order By: Relevance
“…Moreover, these quenching effects could overcome the porosity‐induced emission effect. It has been demonstrated that porosity can efficiently enhance luminescent activity as a result of the interwoven porous network, and thus higher porosity could lead to higher fluorescence . However, HPP‐1 c and HPP‐2 c , which have the highest emission intensity in each series of polymers, only possess moderate porosities.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, these quenching effects could overcome the porosity‐induced emission effect. It has been demonstrated that porosity can efficiently enhance luminescent activity as a result of the interwoven porous network, and thus higher porosity could lead to higher fluorescence . However, HPP‐1 c and HPP‐2 c , which have the highest emission intensity in each series of polymers, only possess moderate porosities.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally,t he signal at around À99 ppm has been assigned to Q n (Si(OSi) n (OH) 4Àn )s pecies,w hich suggests that partial SiÀCb onds were also cleaved. HPP-2 a shows as imilar 29 Si NMR spectrum.T he destruction observedi nt hese polymers can be explained by the distortion of cubic POSS cages linked through rigid connections to form cross-linking networks and the introduction of base as acida dsorbent. [14, 19d, 20, 21c]…”
Section: Synthesis and Characterizationmentioning
confidence: 86%
See 3 more Smart Citations